Let's rewrite the equation with x and y on the left side of the equal sign.
5x-4y=8 --------(1)
3x-3y=3---------(2)
Divide equation (2) by 3,
x - y= 1
now we have,
5x-4y = 8 --------(1)
x - y = 1 ---------(2)
To eliminate x, multiply equation (2) by 5. This makes both the coefficients of x to be 5. Subtract the second equation from the first equation.
5x - 4y = 8
(2) * 5 5x - 5y = 5
(-) (+) (-)
----------------
0x +y =3
Therefore, y=3
Substitute the value of y, in any one of the two equations. Let's substitute y in the second equation.
x-3=1
x=4
x=4 and y=3
Answer:
4.04
Step-by-step explanation:
2.84 + 1.2 = 4.04
Answer:
19000 8000 90000 60000
Step-by-step explanation:
Answer:
You will find the answer easily after doing the steps below.
Step-by-step explanation:
If you have graph paper, this is really easy to do. All you need to do is draw a graph. Then you will number the squares. Next, find the points (-2, 7) and (6, -9). Draw a line connecting the two points you have created.